Environmental education through mural painting activities as to enhance secondary school students' knowledge and awareness on environment - Othman, Rohana; Harun, Rosta; Muda, Azizi; A. Rashid, Noriati; Othman, Fadhilah (IDOSI Publications, 2011)
This study aims to evaluate the impact of environmental education activities and mural painting appreciation in enhancing students' knowledge and awareness to the environment. Environmental education activities were performed in classes for an hour per week for four times. Mural painting activity with the theme of marine ecosystems were conducted outside the classroom for a month. The design of this study was quasi-experimental with a pretest-posttest control group and experimental group, involving 128 students from two ordinary secondary schools in Gombak district, Selangor. The students divided into two groups according to the schools to represent the control and experimental groups, i.e. 64 students for each group. This study used three types of instruments, which are pretest, first post-test and second post-test. Each instrument consists of 20 multiple choice knowledge questions and 18 statements on the environmental awareness based on the 5 Likert scale. The results indicated that the experimental group significantly increased their environmental knowledge and awareness after the experiment, whereas the control group did not.